Case Report: combined surgical and pharmacological management of basal ganglia cryptococcal meningoencephalitis - Zheng, Xiao-Yu; Chen, Ping; Li, Dong-Yue; Chen, Ke-En; Liao, Jian-Cheng; Li, Meng-Hui; Zhang, Mao-Ying (Frontiers in Medicine, 2025)
IntroductionCryptococcal meningoencephalitis involving the basal ganglia is exceedingly rare and poses diagnostic and therapeutic challenges due to its tumor-mimicking presentation. This case underscores the necessity of a multidisciplinary approach integrating surgical intervention and targeted antifungal therapy.Case presentationA 47-years-old immunocompetent female presented with progressive headache and left-sided hemiparesis. Neuroimaging identified a basal ganglia mass initially misdiagnosed as a neoplastic lesion.InterventionsSurgical resection under neuroelectrophysiological monitoring was combined with amphotericin B, flucytosine, and fluconazole.OutcomesComplete lesion excision, symptom resolution, and mild memory deficits at 4-years follow-up.LessonsCombined therapy is pivotal for CM with parenchymal involvement; early surgery may mitigate irreversible neurological sequelae.